Communities and social care in Russia: The role of Muslim welfare provision in everyday life in Russia's Tatarstan region. (September 2014) - Kuznetsova, Irina; Round, John
Based on large-scale surveys and in-depth interviews, this article discusses the role of religion in social welfare and social work in Russia's Republic of Tatarstan, a majority Muslim region. It notes that there is relatively little formal social work provided by large-scale Islam-based groups. However, religious spaces are important as places where social networks are developed, facilitating social welfare provision within wider networks. Locally, mosques rarely provide immediate aid, such as cash transfers, but some engage in long-term targeted provision. The article concludes that as such schemes develop, trust in religious organizations will increase and more people will turn to them in times of need.